Heart failure associated with weaning from mechanical ventilation [Ventilatörden ayirmanin neden olduʇu kalp yetmezliʇi] - (:unkn) unknown (Turkish Anaesthesiology and Intensive Care Society, 2015)
Weaning-induced cardiac dysfunction is an important reason for prolonged mechanical ventilation, and increased morbidity and mortality. Although underlying mechanisms may differ from one patient to another, pulmonary artery catheter, echocardiography, biomarkers, and extra-vascular lung water measurement may help in diagnosing weaning-induced pulmonary edema. Treatment strategies include optimization of flling pressures, reduction of preload and afterload, and delivery of inotropic support if necessary.
Keywords: Cardiac dysfunction; Cardiogenic pulmonary edema; Weaning failure